Response of trichogramma chilonis to infochemicals: an SEM and electrophysiological investigation - Sen, A; Raina, R; Joseph, Mary P.; Tungikar, VB (Biocontrol, 2005)
The external morphology and peripheral olfactory responses of antennal chemoreceptors of Trichogramma chilonis Ishii (Hymenoptera:Trichogrammatidae) to host related stimuli were examined by SEM and EAG technique respectively. The antennae of male and female T. chilonis reveal strong sexual dimorphism in structure as well as in types, density and distribution of individual sensillar types. The female antennae are characterized by the presence of a single uniporous sensilla on the apical tip of the dome and numerous multiporous pitted sensilla. Sensilla common to both males and females include the multiporous plate sensilla, the peg sensilla and trichoid sensilla. Differences between males and females occur with respect to their EAG profiles to 22 chemicals commonly found in plants viz., hexanal, β-pinene, citronellal, terpinene, citronellol, phytol, caryophyllene, R-(+)-limonene, linalool, carvacrol, cis-3-hexen-1-ol, ethanol, α-pinene, trans-2-hexanal, α-phellandrene, amyl acetate, cineole, quinolene, S-(-)limonene, β-myrcene, carvone, terpineol; hexane leaf extracts of three host plants of Helicoverpa armigera (cotton, chickpea and pigeon pea) and hexane scale extracts of adult males and females of H. armigera. Individually, the largest peak amplitudes in females were obtained with citronellal, phytol, caryophyllene, R-(+)-limonene, linalool, carvacrol and citronellol while in males citronellol, caryophyllene, linalool, R-(+)-limonene and amyl acetate caused the highest response. Among the different chemical classes, the largest peak amplitudes in females were obtained with oxygenated monoterpenes, while in males, fatty acid derivatives caused the highest response. In both males and females, the hydrocarbon monoterpenes caused the least response. Thus, the wide spectrum response of Trichogramma chilonis, to a wide group of chemicals belonging to different chemical classes, though varying, nevertheless suggests that using plant information enhances its parasitization efficiency.
Keywords: antennae; Chickpea; cotton; EAG; parasitoid; pigeon pea; scanning electron microscopy; Trichogramma chilonis; Volatiles

Efficacy of 4-methyl-7-hydroxy coumarin derivatives against vectors aedes aegypti and culex quinquefasciatus - Deshmukh, Madhavi; Pawar, Pushpa; Joseph, Mary P.; Phalgune, Usha; Kashalkar, Rajashree; Deshpande, Nirmala R. (Indian Journal of Experimental Biology, 2008)
4-Methyl-7-hydroxy coumarin is considered as a lead molecule as a biopesticide. Its mono bromo and tribromo derivatives were synthesized. Two more derivatives were synthesized by acylation. Compound 1 (3.6,8-tribromo-7-hydroxy-4-methyl-chromen-2-one) was found to be the most potent against IV(th) instar larvae of C. quinquefasciatus and A. aegypti the LC(50) being 1.49 and 2.23 ppm respectively. It showed 100% larval mortality at 25 ppm against A. aegypti and at 10 ppm against C. quinquefasciatus. Compounds 1 and 2 (3,6,8-tribromo-7-hydroxy-4-methyl-chromen-2'-oxo-2H-chromen-7-yl acetate) showed remarkable ovicidal activity. Significant reduction of 80-85%, hatching of eggs of both mosquito species was observed at the highest dose of 100 ppm. The hatched larvae showed 100% mortality in the successive instars. Compounds 3 and 4 (3-bromo-7-hydroxy-4-methyl-chromen-2-one and 3-bromo-4-methyl-2'-oxo-2H-chromen-7-yl acetate) showed moderate activity against both mosquito species.
Keywords: 4-Methyl-7-hydroxy coumarin; Aedes aegypti; Culex quinquefasciatus; Larval mortality; Ovicidal activity

Lavandula gibsoni and plectranthus mollis essential oils: chemical analysis and insect control activities against aedes aegypti, anopheles sfttephensi and culex quinquefasciatus - Kulkarni, Roshan R.; Pawar, Pushpa V.; Joseph, Mary P.; Akulwad, Ambadas K.; Sen, Avalokiteswar; Joshi, Swati P. (Journal of Pest Science, 2013)
Essential oils and acetone extracts from Lavandula gibsoni and Plectranthus mollis, family Lamiaceae, were investigated for their mosquito larvicidal activity against 4th instar larvae of Aedes aegypti, Anopheles stephensi and Culex quinquefasciatus. LC50 values against these three species were 48.3, 62.8 and 54.7 mg/L for L. gibsoni essential oil and 118.5, 137.2 and 128.1 mg/L, respectively, for its acetone extract, while LC50 values for P. mollis essential oil were 25.4, 33.5 and 29.5 mg/L and 195.0, 213.8 and 209.0 mg/L, respectively, for its acetone extract. Repellence of the essential oils was assessed against A. aegypti adults. L. gibsoni essential oil provided 100 % protection for more than 7 h at a concentration of 2.0 mg/cm(2). Under the same conditions, the standard repellent N,N-diethyl-meta-toluamide, at 0.25 mg/cm(2), provided 100 % protection for more than 8 h, while P. mollis essential oil was only weakly repellent. The major components from both essential oils were identified based on GC-MS analysis and linear retention indices. Our results demonstrated promising larvicidal activities of both essential oils against these mosquito species. L. gibsoni essential oil also showed promising repellent activity.
Keywords: Essential oil; Lavandula gibsoni; Mosquito larvicidal activity; Mosquito repellent; Plectranthus mollis